The mechanism of exercise for pain management in Parkinson’s disease - Yu, Wen-Ye; Yang, Qi-Hao; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2022)
The research and clinical applications of exercise therapy to the treatment of Parkinson’s disease (PD) are increasing. Pain is among the important symptoms affecting the daily motor function and quality of life of PD patients. This paper reviewed the progress of research on different exercise therapies for the management of pain caused by PD and described the role and mechanism of exercise therapy for pain relief. Aerobic exercise, strength exercise, and mind-body exercise play an effective role in pain management in PD patients. The pain suffered by PD patients is divided into central neuropathic, peripheral neuropathic, and nociceptive pain. Different types of pain may coexist with different mechanistic backgrounds and treatments. The analgesic mechanisms of exercise intervention in PD-induced pain include altered cortical excitability and synaptic plasticity, the attenuation of neuronal apoptosis, and dopaminergic and non-dopaminergic analgesic pathways, as well as the inhibition of oxidative stress. Current studies related to exercise interventions for PD-induced pain suffer from small sample sizes and inadequate research of analgesic mechanisms. The neurophysiological effects of exercise, such as neuroplasticity, attenuation of neuronal apoptosis, and dopaminergic analgesic pathway provide a sound biological mechanism for using exercise in pain management. However, large, well-designed randomized controlled trials with improved methods and reporting are needed to evaluate the long-term efficacy and cost-effectiveness of exercise therapy for PD pain.